Malignant Proliferating Pilar Tumor: A Rare Mimic of Squamous Cell Carcinoma. (28th October 2020) - Beversdorf, W; Rinker, E
Abstract: Introduction/Objective: Proliferating pilar tumor is a rare cutaneous adnexal neoplasm, closely resembling and potentially misdiagnosed as conventional squamous cell carcinoma. Malignant forms are recognized; however, differentiating criteria have not been firmly established due to their exceptional rarity. Prognosis is variable, with recurrence or metastasis reported in up to 25% of patients within a very small data set. Methods: We present a case of a 31 year old male who underwent excision of a posterior neck mass clinically presumed to be a recurrent benign cyst in 2018. Initial excision was performed at an outside institution approximately 10 years prior, and a pathology report was not included in his record. Results: Our resection specimen contained a 5.5 cm lobulated, cystic and solid mass involving the dermis and subcutis with superficial ulceration. Tumor histology was consistent with malignant proliferating pilar tumor as described in other reported cases, showing a proliferation of pleomorphic squamous cells infiltrating the dermis and associated desmoplasia. The tumor featured abundant pilar keratinization with focal necrosis and increased mitotic activity. Numerous smaller pilar cysts exhibiting varying degrees of squamous atypia studded the periphery of the dominant mass. The immunohistochemical profile of this case also exhibited similarities to other reports, with focal positivity for calretinin and CD34 as well as an increased Ki-67 proliferative index (up to 70–80%). While other reports document diffuse expression of p53, our case demonstrated complete absence of p53 staining. Conclusion: We present this case to highlight the importance of recognizing pilar differentiation within squamous lesions, examine pathologic features associated with malignant behavior, and discuss the relationship between histologic characteristics and clinical outcomes in this exceedingly rare tumor group.